Strategi Pemasaran Untuk Meningkatkan Minat Berkunjung Wisatawan Di Taman Celosia Jokis Palembang - Aldrian, Axelking; Widagdo, Herry (MDP Student Conference, 2024)
The aim of this research is to analyze marketing strategies to increase tourist interest in visiting Celosia Jokis Park in Palembang partially and this research is to analyze marketing strategies to increase tourist interest in visiting Celosia Jokis Park in Palembang simultaneously. The method used for data collection was distributing questionnaires to 200 respondents. The type of research used is descriptive. The sampling technique uses nonprobability sampling with a purposive sampling method and uses the SPSS 21 application. The results of this research show that the partial test (t-test) of promotion variables and price have a positive and significant effect on visiting interest. The simultaneous test (F-test) proves that the independent variables are promotion and price, which have a positive and significant effect on the dependent variable, namely interest in visiting.